2024
DOI: 10.1039/d4tb00437j
|View full text |Cite
|
Sign up to set email alerts
|

Design-encoded dual shape-morphing and shape-memory in 4D printed polymer parts toward cellularized vascular grafts

Saswat Choudhury,
Akshat Joshi,
Vageesh Singh Baghel
et al.

Abstract: Current additive manufacturing technologies wherein as-printed simple two-dimensional (2D) structures morph into complex tissue mimetic three-dimensional (3D) shapes are limited to multi-material hydrogel systems, which necessitate multiple fabrication steps and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Self-folding polymers can sometimes create blood vessels, which can then be organized into multilayered tubelike structures encapsulated with various cell types. 120,121 Several recent studies have reported a 4D fabrication strategy to produce these intricate designs, 122,170 also allowing the synthetic cardiovascular stent to be delivered and performed at the site in a minimally invasive manner. In most investigations, the shape-morphing feature is attempted to be achieved under physiological conditions.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…Self-folding polymers can sometimes create blood vessels, which can then be organized into multilayered tubelike structures encapsulated with various cell types. 120,121 Several recent studies have reported a 4D fabrication strategy to produce these intricate designs, 122,170 also allowing the synthetic cardiovascular stent to be delivered and performed at the site in a minimally invasive manner. In most investigations, the shape-morphing feature is attempted to be achieved under physiological conditions.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%